A new and critically endangered species of Turraea (Meliaceae) endemic to the island of Mauritius - Baider, Claudia; Florens, F. B. Vincent (Phytotaxa, 2016)
Turraea dargentiana (Meliaceae), a new endemic species from Mauritius, is described, its ecology and conservation are discussed, and a revised key to the Mascarenes species of Turraea is provided. Turraea dargentiana is the smallest and the only species of the genus known to display cryptic dioecy in the Mascarenes, and also the only one possessing adult leaves that are often irregularly lobed in their distal half. The species appears restricted to the understory of relatively well-preserved native vegetation remnants in a few wet mountain tops and ridges. Given this restricted distribution, a small total population size and the encroachment of invasive alien plants, which are causing continued degradation of the species’ habitat, the species should be considered as Critically Threatened according to the Red List Categories and Criteria of the International Union for the Conservation of Nature.